DOP65 The association of faecal calprotectin level and combined mucosal and transmural healing in patients with Crohn's disease. (25th January 2019) - Noh, S; Oh, E H; Park, S H; Lee, J B; Kim, J Y; Park, J C; Kim, J; Ham, N; Song, E M; Park, S H; Hwang, S W; Yang, D H; et al.
Abstract: Background: Combined mucosal and transmural healing of inflammatory lesions in patients with Crohn's disease (CD) are regarded as the predictor of favourable outcomes. However, non-invasive markers for predicting combined mucosal and transmural healing is needed for patients' acceptance and tighter monitoring. This study aimed to evaluate the role of faecal calprotectin (FC) as a non-invasive marker for predicting combined mucosal and transmural healing in Korean patients with CD on anti-TNF therapy. Methods: A total of 226 CD patients on anti-TNF therapy who underwent endoscopic evaluation, radiologic evaluation and FC measurement between August 2017 and July 2018 were enrolled in this study. Endoscopic mucosal healing was independently assessed by two certified endoscopists and defined as no visible ulcers related to CD in colon and small bowel. Transmural healing in computed tomography enterography or magnetic resonance enterography was assessed by one certified radiologist. Deep healing was defined as a combination of mucosal and transmural healing. Results: Out of 226 patients, 157 (69.5%) were men, and the median age at diagnosis of CD was 24 years (IQR, 18–29 years). The median disease duration prior to FC measurement was 10 years (IQR, 6–14 years). At the time of evaluation, ileocolonic location was observed in 181 patients (80.1%) and stricturing or penetrating behaviour was observed in 153 patients (67.7%). Out of 226 patients, 56 (24.8%) had deep healing, 34 (15.0%) had mucosal healing without transmural healing, 33 (14.6%) had transmural healing without mucosal healing, and 103 (45.6%) had both mucosal and transmural inflammation. Faecal calprotectin (A), CRP (B), ESR (C), and albumin (D) in those with mucosal healing, transmural healing, and deep healing. MH, mucosal healing; TH, transmural healing. The median level of FC in patients with deep healing was lower than that of other groups (55.1 mg/kg vs. 305.0 mg/kg, p < 0.001). The FC cut-off level of 164.5 mg/kg indicated deep healing with a sensitivity and specificity of 0.659 and 0.839, respectively (area under the receiver-operating characteristic curve, 0.797; 95% confidence interval, 0.728–0.865). Receiver-operating characteristic (ROC) curve analysis of each marker to predict deep healing in patients with Crohn's disease ( n = 226). FC, faecal calprotectin; AUC, area under curve. Conclusions: The FC level could be used as a reliable indicator for combined mucosal and transmural healing in patients with Crohn's disease.